2016
DOI: 10.3390/molecules21091248
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Attenuates Myocardial Ischemia/Reperfusion Injury via Akt/GSK-3β/HIF-1α Signaling in Rat H9c2 Cardiomyocytes

Abstract: Myocardial ischemic/reperfusion injury results from severe impairment of coronary blood supply and leads to irreversible cell death, with limited therapeutic possibilities. Asiatic acid is a pentacyclic triterpenoid derived from the tropical medicinal plant Centella asiatica and serves a variety of bioactivities. In this study, we determined the effect of asiatic acid on myocardial ischemia/reperfusion injury and investigated the underlying mechanisms, using an in vitro rat H9c2 cardiomyocytes model of oxygen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 47 publications
(48 reference statements)
2
47
0
Order By: Relevance
“…Asiatic acid (AA) is a natural pentacyclic triterpene derived from Centella asiatica (Apiaceae family). A recent study by Huang et al suggested AA could protect rat H9c2 cardiomyocytes against oxygen‐glucose deprivation/reoxygenation induced apoptosis partly via the Akt/GSK‐3β/HIF‐1α pathway. Kim et al investigated the effect of AA treatment on the miRNA expression profiles of human non‐small cell lung cancer A549 cells and found miR‐1290 was significantly increased by 44.56 fold, suggesting AA may play its biologic role through regulating miR‐1290.…”
Section: Introductionmentioning
confidence: 99%
“…Asiatic acid (AA) is a natural pentacyclic triterpene derived from Centella asiatica (Apiaceae family). A recent study by Huang et al suggested AA could protect rat H9c2 cardiomyocytes against oxygen‐glucose deprivation/reoxygenation induced apoptosis partly via the Akt/GSK‐3β/HIF‐1α pathway. Kim et al investigated the effect of AA treatment on the miRNA expression profiles of human non‐small cell lung cancer A549 cells and found miR‐1290 was significantly increased by 44.56 fold, suggesting AA may play its biologic role through regulating miR‐1290.…”
Section: Introductionmentioning
confidence: 99%
“…Triptolide has been shown to potentially exhibit anti-inflammatory and autoimmune-suppressive activities, accompanied by severe toxicities, such as cardiac and liver damage [84]. It has been demonstrated that selective inhibition of GSK-3β by SB216763 may significantly ameliorate the adverse effects of triptolide in H9c2 cells through inhibition of CyP-D phosphorylation and modulation of Bcl-2 family proteins, leading to desensitization of mPTP and prevention of mitochondrial apoptosis [85].…”
Section: Natural Compounds Regulate Mitochondrial Activity Through Gsmentioning
confidence: 99%
“…Proanthocyanidins, an effective free radical scavenger, ameliorates anoxia-reoxygenation injury through activation of PI3K-Akt-GSK-3β signaling pathway and mK ATP channel pathway in myocardial cells [82]. Asiatic acid, a pentacyclic triterpenoid isolated from Centella asiatica , exhibits protective effects against myocardial I/R injury, as indicated by improved mitochondrial functions through Akt-GSK-3β-HIF-1α signaling in hypoxic H9c2 cells [83]. …”
Section: Natural Compounds Regulate Mitochondrial Activity Through Gsmentioning
confidence: 99%
“…The protective effect of C. asiatica extracts and its triterpenes against cardiac hypertrophy and myocardial ischemia have been demonstrated in several in vitro studies (▶ Table 1) [31][32][33][34]. These studies suggested that asiatic acid, one of the triterpenes of C. asiatica, exerts protective effects in cardiomyocytes by activating or deactivating key signaling pathways involved in the pathogenesis of cardiac hypertrophy and myocardial ischemia.…”
Section: Cardioprotective Effects Of C Asiatica and Its Triterpenesmentioning
confidence: 99%